Sigmoid colon schwannoma difficult to distinguish from peritoneal dissemination 13 years after pancreatic neuroendocrine tumor surgery - Kazunobu Suzuki; Takuya Shiraishi; Ikuma Shioi; Naoya Ozawa; Takuhisa Okada; Katsuya Osone; Takaaki Sano; Kenichiro Araki; Hiroomi Ogawa; Akihiko Sano; Makoto Sakai; Makoto Sohda; et al. (Surgical Case Reports)
Abstract Background Schwannoma, which clinicians sometimes struggle to diagnose, is a tumor arising from Schwann cells of peripheral nerves, often in the soft tissues and rarely in the gastrointestinal tract. Pancreatic neuroendocrine tumor (PNET) is rare among pancreatic tumors, and recurrence can occur long after resection. Here, we were presented with a case where a sigmoid colon schwannoma was difficult to distinguish from a postoperative recurrence of PNET and was diagnosed after laparoscopic resection. Case presentation A 51-year-old man was diagnosed with PNET (NET G2) after a distal pancreatectomy (DP) 13 years ago. The patient underwent hepatectomy due to liver metastasis 12 years after initial radical surgery. The follow-up magnetic resonance imaging (MRI) after hepatectomy showed pelvic nodules, and laparoscopic surgery was performed for both diagnosis and treatment because peritoneal dissemination of PNET could not be ruled out. Since the tumor was in the sigmoid colon, a partial colon resection was performed. The histopathological diagnosis was a schwannoma, and the patient was discharged on the seventh postoperative day. Conclusions We experienced a case of sigmoid colon schwannoma that was difficult to differentiate from peritoneal dissemination of PNET and was later diagnosed after laparoscopic resection. In addition, this case involved a long-term postoperative recurrence of PNET that was amenable to radical resection, further establishing the importance of long-term imaging follow-up.